2016
DOI: 10.3390/md14070121
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological Evaluation of Low Molecular Weight Fucoidan in Vitro and in Vivo

Abstract: For a long time, fucoidan has been well known for its pharmacological activities, and recently low molecular weight fucoidan (LMF) has been used in food supplements and pharmaceutical products. In the present study, LMF was extracted from Laminaria japonica by enzyme hydrolysis. The toxicity of LMF in mouse and rat models was determined by many methods, such as total arsenic content, bacterial reverse mutation assay, chromosome aberration assay, and in vivo micronucleus assay. The present findings showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 42 publications
2
28
0
1
Order By: Relevance
“…As yet no reports about toxic effects of marine APS are available and no undesirable effects of overdose and sensitivity to polysaccharides are reported [3]. One of the studies which reported that consumption of fucoidan at the recommended dose (2,000 mg/kg bw/day) did not cause any toxicological indications was performed by Hwang et al [144]. Neither toxicity nor mutagenicity of fucoidan from L. japonica was observed at concentration of 5,000 µg/mL [144] and no toxicity was measured in any blood samples when consuming F. vesiculosus extract with 85% fucoidan (300 mg) for 12 weeks [145].…”
Section: Brown Algae Sulfated Polysaccharides As Drug Delivery Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…As yet no reports about toxic effects of marine APS are available and no undesirable effects of overdose and sensitivity to polysaccharides are reported [3]. One of the studies which reported that consumption of fucoidan at the recommended dose (2,000 mg/kg bw/day) did not cause any toxicological indications was performed by Hwang et al [144]. Neither toxicity nor mutagenicity of fucoidan from L. japonica was observed at concentration of 5,000 µg/mL [144] and no toxicity was measured in any blood samples when consuming F. vesiculosus extract with 85% fucoidan (300 mg) for 12 weeks [145].…”
Section: Brown Algae Sulfated Polysaccharides As Drug Delivery Systemmentioning
confidence: 99%
“…One of the studies which reported that consumption of fucoidan at the recommended dose (2,000 mg/kg bw/day) did not cause any toxicological indications was performed by Hwang et al [144]. Neither toxicity nor mutagenicity of fucoidan from L. japonica was observed at concentration of 5,000 µg/mL [144] and no toxicity was measured in any blood samples when consuming F. vesiculosus extract with 85% fucoidan (300 mg) for 12 weeks [145]. Acute toxicity results by Lim et al [146] classified S. binderi extract as category 5 (unclassified) according to the OECD Guideline since no mortality in rats was observed at the highest dosage (2,000 mg/kg).…”
Section: Brown Algae Sulfated Polysaccharides As Drug Delivery Systemmentioning
confidence: 99%
“…Toxicology studies of the low-molecular-weight fucoidan from L. japonica have indicated its potential use as a food supplement, as neither toxicity nor mutagenicity was observed at the concentration of 5,000 μg/mL (Hwang, Yan, Lin, Li, & Lin, 2016). Different toxicology studies, including bacterial reverse mutation assays, in vivo micronucleus assays, total arsenic content, and chromosome aberration assays, have shown that consumption of fucoidan at the recommended dose of up to 2,000 mg/kg bw/day did not cause any toxicological indications (Hwang et al, 2016). Consumption of F. vesiculosus extract containing 85% fucoidan (300 mg) for 12 weeks was tested with 122 people with osteoarthritis (Myers et al, 2016).…”
Section: Safety and Toxicity Of Seaweed Polysaccharidesmentioning
confidence: 99%
“…Owing to their high molecular weight, therapeutic applications of native fucoidans face many challenges including structure elucidation, solubility, manufacturing, and handling [63,116], in addition to safety as a food supplement [175]. Structure elucidation and quantitation of native fucoidans is highly complicated and requires advanced or hyphenated spectroscopic techniques such asHPLC-MS/MS as it applied in Sea Cucumbers fucoidans [176,177].…”
Section: Enzymatic Modification Of Native Fucoidansmentioning
confidence: 99%